Cryptic Marine Diversity in the Northern Arabian Gulf: An Integrative Approach Uncovers a New Species of Oyster (Bivalvia: Ostreidae), Ostrea oleomargarita. (4th July 2022) - Salvi, Daniele; Al-Kandari, Manal; Oliver, P. Graham; Berrilli, Emanuele; Garzia, Matteo
Abstract : Animal biodiversity is greatly underestimated in nontemperate marine regions, especially for intertidal benthic organisms such as oysters. Recent surveys in the northern Arabian Gulf suggest the presence of numerous unidentified species, some of which form shallow reef ecosystems while others are cryptic and found under rocks. In this study, we focused on small oysters from Kuwait, which show typical characteristics in common with the genus Ostrea except for the presence of lophine chomata that would link it to the genera Lopha, Dendostrea, and Alectryonella . Phylogenetic analyses based on mitochondrial and nuclear markers unambiguously placed the Kuwait oyster within the Ostreinae as a sister to the Japanese species Ostrea futamiensis . The hypothesis that the Kuwait oyster represents a new species was assessed with phylogenetic and species delimitation methods combined with a morphological assessment. Results corroborated the Kuwait oysters as a new species herein described as Ostrea oleomargarita Oliver, Salvi, and Al-Kandari, sp. nov. The phylogeny of the Ostreinae shows extensive disagreement between morphology-based genera and phylogenetic clades. The genus Ostrea is polyphyletic, and the form and distribution of taxonomic characters such as chomata are not as definitive as suggested in previous studies. This study, along with other recent investigations, confirmed the Arabian Gulf as a key region for discovering marine animal diversity and suggested a possible biogeographic divide between the Eastern and Western Indo-Pacific. A pattern that has been documented in a growing number of taxa and that warrants further research attention.